SUSTRA LOWIS: STRENGTHENING TOURISM INDUSTRY TO REALIZE INDONESIA AS GLOBAL MARITIME AXIS - Azizi, Pipin Nur (Jurnal Indonesia Emas PPI Dunia, 2018)
Indonesia is the worldâs largest archipelago country and it has coastline stretching from Sabang to Merauke with more than 17.500 islands. As a maritime country, Indonesia has potential on marine tourism which can be a backbone of economy amid the global economic turmoil. However, the performance of Indonesian tourism has not shown satisfactory results if viewed from the data of foreign tourist visits which is left behind with neighboring countries. The implementation of SUSTRA LOWIS (Sustainable Tourism Strategy Based on Local Wisdom) is expected to increase the role of Indonesias marine tourism sector to the economy by improving the quality of tourism management and human resources. Development of tourism must involve the role of society, but government is less concerned about it.The purpose of this paper is to create innovations to enhance the role of marine tourism industry to Indonesian economy, explaining that Indonesia has tremendous maritime potential and can be utilized for the collective interest and provide an overview to the government on programs that can be implemented for the marine tourism industry. This type of research is descriptive analysis. The study aims to analyze and describe the implementation of SUSTRA LOWIS as an effort to realize Indonesia as the worldâs  maritime axis. Data were collected through observation and literature studies. The research concluded that SUSTRA LOWIS (Sustainable Tourism Strategy Based on Local Wisdom) has five main sectors for the development of marine tourism those are, Tourism Management Sector (TMS), Tourism Training Sector (TTS), Business Improvement Sector (BIS), Technology Based Tourism Sector (TBTS), and Maritime Education Sector (MES). These five sectors have programs that can support the development of marine tourism thoroughly and sustainably to realize Indonesia as the worldâs  maritime axis.